Epidemiological characteristics and influencing factor of non-occupational carbon monoxide poisoning during 2007—2018 in Shanghai - Fei’er CHEN; Meizhu PAN; Huihui XU; Chunyang DONG; Qing GU; Qi’ang JIN; Jianghua ZHANG; Yewen SHI; Hailei QIAN; Chen WU (环境与职业医学, 2022)
BackgroundNon-occupational carbon monoxide (CO) poisoning is a public health problem that seriously affect people’s health and lives. ObjectiveTo describe the prevalence of non-occupational CO poisoning during 2007—2018 in Shanghai, analyze its epidemiological characteristics and potential influencing factors, and explore effective prevention and control measures. MethodsDaily reported non-occupational CO poisoning cases and meteorological factors from 2007 to 2018 were collected in Shanghai, epidemiological characteristics were analyzed by descriptive epidemiology methods, and a distributed lag nonlinear model was used to assess the association between temperature and non-occupational CO poisoning. ResultsA total of 2264 non-occupational CO poisoning events and 3866 cases from 2007 to 2018 were reported in Shanghai, including 59 death cases. More than half of the poisoning cases were female (56.3%), and young adults accounted for more cases than any other age group (54.8%). The poisoning events mainly occurred in winter (from December to next February); however, cases reported in summer increased in recent years. The peak period of the events was from 20:00 to 24:00. Households (85.2%) and restaurants (8.0%) were the common places of non-occupational CO poisoning events, and the main cause was improper use of gas water heater (36.9%). A nonlinear curve was found between daily average temperature of current day and the occurrence of non-occupational CO poisoning. Temperature was negatively associated with the risk of non-occupational CO poisoning when the temperature was lower than 9.6 ℃, while a positive association was found during 9.7-26.0 ℃. ConclusionWinter is a high season for non-occupational CO poisoning in Shanghai, rising cases reported in summer is also worthy of attention. Supervision should be strengthened to ban sales of unqualified gas water heaters, and health education on CO poisoning prevention and control should be conducted through multiple channels, in order to reduce the incidence of CO poisoning.